Developing a fertilizer strategy for sub-Saharan Africa - Sanders, J.H.; Ahmed, M. (ASA, 2001)
With the increasing information now available on responding to the soil fertility problem in sub-Saharan Africa, better policy should be possible. Previously, there was not much acknowledgment in the literature that at the really low levels of N and P in much of the continent it was going to be necessary to use both organic and inorganic fertilizers on food crops. Now in a recent American Society of Agronomy publication this has become conventional wisdom among both soil scientists and economists (Buresh et al., 1997). Previously mention of input subsidies was almost heretical especially if there were World Bank personnel around. Now fertilizer subsidies are back on the agenda at least for discussion. In this chapter, we first review the national soil fertility programs in Burkina Faso and Ethiopia. Second, we look at two different approaches to subsidizing the soil fertilization decision. Then we return to the question of this panel: Are there any shortcuts to achieve sustainable farming systems in Africa? Finally, some general policy and research implications are made.